2020
DOI: 10.1002/ajoc.201900704
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Synthesis of N‐Substituted Phenanthridinones and Spiro‐isoindolinones: C(sp2)−N and C(sp2)−O Coupling through Radical Pathway

Abstract: Iodine-mediated intramolecular coupling of CÀ H and NÀ H bonds through radical pathways has been achieved for the synthesis of substituted phenanthridinones from 2phenylbenzamides using iodine, succininmide and di-tertbutylperoxide (DTBP) oxidant in dichloroethane at 130°C. The developed protocol provides substituted phenanthridinones, particularly N-alkyl substituted, which are difficult to access either by base-mediated or transition-metal-catalyzed methodologies due to acidic nature of the CÀ H bond adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…However, the substrates of such cylizations through sequential aryl‐aryl and N ‐aryl coupling is rather limited, which often focuses on N ‐methoxybenzamides. In addition, the synthesis of substituted phenanthridinones from 2‐phenylbenzamides was also achieved with iodine‐mediated intramolecular coupling reactions through radical pathways [3g] . However, few report was recorded with N ‐arylbenzamides as the substrate for direct cyclization to enrich the N ‐aryl phenanthridinone family.…”
Section: Methodsmentioning
confidence: 99%
“…However, the substrates of such cylizations through sequential aryl‐aryl and N ‐aryl coupling is rather limited, which often focuses on N ‐methoxybenzamides. In addition, the synthesis of substituted phenanthridinones from 2‐phenylbenzamides was also achieved with iodine‐mediated intramolecular coupling reactions through radical pathways [3g] . However, few report was recorded with N ‐arylbenzamides as the substrate for direct cyclization to enrich the N ‐aryl phenanthridinone family.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Verma et al reported an intramolecular CÀ H amination in 2phenyl benzamides for CÀ N bond formation in phenanthridinones (Scheme 3). [10] This metal-free oxidative cyclization occurred using DTBP, iodine, succinimide in DCE at 130 °C for 12 h to afford mainly N-alkylated phenanthridinones which otherwise were difficult to synthesize conventionally. A radical pathway has been proposed for the reaction.…”
Section: Reactions Involving Radical Intermediatesmentioning
confidence: 99%
“…When the substrate was bearing OTBS-group, the intermediate 29-C delivered spirolactam 35. Later, Verma et al reported a cyclization of 2-phenylbenzamides for the preparation of phenanthridinones using iodine, succinimide, and di- tert -butylperoxide (DTBP) as oxidant [ 125 ]. It has been shown that 2′-iodo-[1,1′-biphenyl]-2-carboxamide could be cyclized into phenathridinone under Ni-catalysis in the presence of boronic acid [ 126 ].…”
Section: N –Aryl Coupling Reactions For Phenanthridinone Synthesismentioning
confidence: 99%